Osteopromotive effects of polyhydroxyalkanoates in an animal model / Shirley Koh Pui Ling - Koh, Shirley Pui Ling (2009)
The biocompatibility and potential osteoconductive properties of medium-chain-length polyhydroxyalkanoates (mcl-PHA) in bone was investigated using the rabbit mandible as the animal model. The PHA was produced by a bacteria Pseudomonas putida using saponified palm kernel oil (SPKO) as carbon source. Twelve New Zealand white rabbits weighing between 2.5 kg to 3.5 kg were used. Twenty four of full thickness critical size (15 mm × 10 mm) defects were created in rabbit mandibles bilaterally. In each rabbit, the PHA sheet of size 19 mm × 27 mm was wrapped over the defect on one side. The remaining defects were left empty as controls. The rabbits were sacrificed at time intervals between 3 to 12 weeks and the defects together with the surrounding tissues were retrieved and prepared for histological analysis using the Exakt Cutting System. The rabbits remained in good health with minimal infection throughout the course of this study. Host tissue response to PHA, the quantity and quality of new bone regeneration were evaluated. Results showed no adverse host tissue response. The comparison of average mean new bone volume between PHA and control groups were done at 3-, 6-, 9- and 12-week healing intervals. It was found that the average mean new bone volume of the PHA treatment and the controls increased as the time intervals increased but at different amounts. The average mean new bone volume for PHA groups were 3.17 ± 0.58 % at 12-weeks, 1.41 ± 0.38 % at 9-weeks, 1.40 ± 0.72 % at 6-weeks and 0.90 ± 0.10 % at 3-weeks. These values were compare to the control groups - 1.70 ± 0.65 % at 12-weeks, 0.67 ± 0.24 % at 9-weeks, 0.10 ± 0.18 % at 6-weeks and 0.30 ± 0.15 % at 3-weeks and these differences were statistically significant (p < 0.05). Apart from that, there were physical changes observed in the implanted PHA and this may suggest a possibility of biodegradation that had taken place. These findings predicted that PHA is biocompatible in bone and has osteoconductive properties.